Effectiveness and safety of long-term dabigatran among patients with non-valvular atrial fibrillation in clinical practice: J-Dabigatran Surveillance. Issue 2 (August 2019) - Inoue, Hiroshi; Uchiyama, Shinichiro; Atarashi, Hirotsugu; Okumura, Ken; Koretsune, Yukihiro; Yasaka, Masahiro; Yamashita, Takeshi; Taniguchi, Atsushi; Fukaya, Taku; ,
Highlights: Three quarters of Japanese atrial fibrillation patients received reduced dose of dabigatran. The reduced dose group had higher event rates than the standard dose group. In multivariate analysis, dabigatran doses were not associated with outcome events. Abstract: Background: The effectiveness and safety of dabigatran etexilate (DE) have not been elucidated thoroughly in clinical practice for Japanese patients with non-valvular atrial fibrillation (NVAF). In particular, those of DE at a reduced dose due to dose reduction recommendations (DRR) remain unknown. Methods: NVAF patients who had newly initiated DE treatment for prevention of thromboembolic events between December 2011 and November 2013 were enrolled. They were followed until August 2016. Outcome events included thromboembolism, major bleeding, and all-cause death. Results: The study group consisted of 6443 patients (mean age, 70.9 years; male, 66.9%; and mean CHADS2 score, 1.8). During a follow-up period of 610 days (median), stroke, transient ischemic attack (TIA), and systemic embolism (SE) occurred at 1.4%/year for DE 110 mg twice daily (BID) (DE220, n  = 4759) and 0.8% for dabigatran 150 mg BID (DE300, n  = 1571, unadjusted p  = 0.0317). Major bleeding occurred at 1.3 and 0.6%/year for DE220 and DE300, respectively (unadjusted p  = 0.0097). All-cause death occurred at 1.5 and 0.5%/year for DE220 and DE300, respectively (unadjusted p  = 0.0005). When patients were divided into four groups based on DRR and DE doses (DE300 groups meeting and not meeting DRR, and DE220 groups meeting and not meeting DRR), incidence rates of stroke/TIA/SE and major bleeding differed among the four groups (unadjusted p  = 0.0026 and 0.0194 for trend, respectively); DE220 group meeting DRR had the highest rates (1.7% and 1.4%/year, respectively). However, in multivariate analysis, no differences between doses were observed regarding any outcomes. Conclusions: The present results are indicative of the favorable benefit-risk profile of dabigatran in Japanese clinical practice. Dabigatran dose was not independently associated with thromboembolic and bleeding events in Japanese NVAF patients.